Development of a porous thermosyphon facility with liquid-cooled condenser - Tan, Guohao. (2011)
Over the years, improvements in technology have inevitably led to increasing power densities of high speed electronic devices which have exceeded the capabilities of conventional cooling methods. The two-phase cooling thermosyphon has proven to give promising results in the thermal management for high heat loads. A thermosyphon system consists of a condenser, an evaporator base simulating a heat dissipating electronic module and a coolant chamber. This project investigated the effects of condensation mode, boiling material, working fluid, height of graphite foam, surface roughness and inner pores on the heat transfer performance of a thermosyphon. Air cooled condenser was replaced with water cooled condenser which was found to be more capable in maintaining chamber pressure and yielded lower wall temperature. Poco block foam attained higher heat transfer coefficient than copper block. Three working fluids, namely FC-72, HFE-7000 and de-ionized water were used and experiments performed using HFE-7000 yielded the lowest wall temperature. The height effect of graphite foams being implemented as an attachment onto the evaporator base was studied and the tallest graphite foam achieved the lowest wall temperature and the highest heat transfer coefficient. Copper block of higher roughness value performed better as compared to the smooth one. The inner pores of graphite foam found to have a difference in heat transfer and its performance was verified by high speed imaging recording.